Interacting with TV: report of a user experience evaluation considering affective state - Menezes, Ewerton M.; Piccolo, Lara S. G.; Tambascia, Cláudia A. (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2012: Proceedings of the 18th Brazilian Symposium on Multimedia and the Web, 2012)
The way people relate with technology nowadays requires more from human-computer interaction methods: good usability is an essential condition, but users expect also a pleasant and funny experience, especially when entertainment is the purpose. This paper reports the usability evaluation of games and of an e-commerce application for interactive TV, which considered users' affective state, and highlights this approach benefits to analyze the interaction design.